Responses of Upland NERICA Rice to Fertiliser Application and Fallow Management in Different Agro-Ecological Zones of Benin Republic - Omonlola Nadine Worou; Thomas Gaiser; Mouinou Attanda Igué; Charlemagne Gbemavo; Brice Augustin Sinsin (European Scientific Journal, ESJ, 2017)
Recent findings reported that introduction of legumes as an intercrop or in rotation to minimize external inputs can reverse the declining of soil fertility in upland rice agrosystem and so improve the productive capacity of farms. The objectives of the study were to assess (1) the effects of rotation of upland rice with other crops, of fertiliser application and of rice varieties on rice yield and (2) the interaction effects of rotation, fertiliser application and variety on rice production. An experiment was carried out from 2011 to 2012 in 2 zones in Benin Republic, West Africa. Three rice rotation treatments were established where in the year preceding rice cropping the following pre-crops were grown: (1) natural fallow regrowth (2) sole cowpea crop and (3) cowpea/maize intercrop. The following year, 3 NERICA varieties were cultivated in the three pre-crop treatments with and without fertiliser application. With respect to combined effect of NP mineral fertiliser and rotation, a consistent increase in rice yield over all varieties was only observed with maize-cowpea intercrop preceding rice in the Guinean zone. Improved fallow with cowpea combined with fertiliser was beneficial for NERICA 2 and NERICA 4 in the Sudano –Guinean zone and with NERICA 1 and NERICA 4 in the Guinean zone. Rice in rotation with maize-cowpea intercrop and in combination with NP mineral fertiliser can easily fit into the current smallholder farming systems under rain-fed conditions in the Guinean zone, but is not recommendable for the Sudano- Guinean zone.